Analisis Perlindungan dan Upaya Hukum Organisasi Ikatan Notaris Indonesia terhadap Notaris yang Diduga Melakukan Tindak Pidana Terkait Akta yang Dibuatnya: Studi di Pengwil Sumatera Utara - Anita Rahmah; Hasim Purba; Suprayitno (CV Rewang Rencang, 2025)
The Notary profession as a public official holds a strategic role in Indonesia's legal system, regulated through the Notary Position Law (UUJN) and the Notary Code of Ethics (KEN) by the Indonesian Notary Association (INI). However, increasing cases of alleged criminal acts by Notaries in North Sumatra raise concerns about the effectiveness of INI's legal protection. This empirical juridical research analyzes the implementation of UUJN and KEN and INI's role in providing legal protection. Results show that INI's legal protection remains suboptimal due to implementation gaps in norms, resource limitations, and weak coordination with the Notary Honor Council (MKN) and law enforcement agencies, necessitating structural reforms to ensure legal certainty for notaries.